Gender, playfulness, and creativity: a perspective of human resource development. (28th December 2019) - Lin, Liang-Hung; Ho, Yu-Ling; Lee, Tai-Yu; Lin, Wei-Hsin Eugenia
This study explores the differences between male and female employees in individual creativity and personal playfulness. Findings of this study showed that male employees have more personal playfulness than female employees, whereas female employees who received higher education and have more support from their husband tend to show higher levels of personal playfulness and creativity. Moreover, personal playfulness can increase employee creativity and such increase differs between male and female employees. By considering playfulness in the workplace as a personality trait, this study therefore contributes to the existing literature of human resource development.